Gepants against SARS COV-2 Main Protease - Ferrari, I.V.; Mario, M. Di; Narducci, R.; Patrizio, P. (International Journal of Scientific Research in Computer Science and Engineering, 2021)
in the present in Silico work, we focused on “Gepants", used for the treatment of Migraine, as a potential target of SARS-COV-2 Main Protease, using Molecular Docking Analysis. From Autodock Vina and Autodock 4 results, we found out Zavegepant (as knownVazegepant), which has significant binding energy and excellent affinity against SARS-COV-2 Main pro. Indeed, it has shown a high Binding Energy score, of about -11.43 kcal mol -1, and an excellent estimation of Inhibitory constant Ki 4.19 nM.